15 Years' production data on Dorper sheep at Katumani Research Station, Machakos - King' Oku, J.M.; N'Thome, J.; Ogutu, E.; Rakoczi, G. (1975)
Overall birth rate 78%, overall twining rate 10%, average birth weight 3.6kg, stocking rate influences certain productions, e.g., a 75% increase in stocking rate decreased twinning by 46%, increased lamb losses by 186%; however, output from pastures in terms of lamb weaning weight was only 8% less in high stocking rate period than in low.